Stem cell expression of the AML1/ETO fusion protein induces a myeloproliferative disorder in mice - Fenske, Timothy S. (National Academy of Sciences, 2004)
The t(8;21)(q22;q22) translocation, present in 10-15% of acute myeloid leukemia (AML) cases, generates the AML1/ETO fusion protein. To study the role of AML1/ETO in the pathogenesis of AML, we used the Ly6A locus that encodes the well characterized hematopoietic stem cell marker, Sca1, to target expression of AML1/ETO to the hematopoietic stem cell compartment in mice. Whereas germ-line expression of AML1/ETO from the AML1 promoter results in embryonic lethality, heterozygous Sca1(+/AML1-ETO ires EGFP) (abbreviated Sca(+/AE)) mutant mice are born in Mendelian ratios with no apparent abnormalities in growth or fertility. Hematopoietic cells from Sca(+/AE) mice have markedly extended survival in vitro and increasing myeloid clonogenic progenitor output over time. Sca(+/AE) mice develop a spontaneous myeloproliferative disorder with a latency of 6 months and a penetrance of 82% at 14 months. These results reinforce the notion that the phenotype of murine transgenic models of human leukemia is critically dependent on the cellular compartment targeted by the transgene. This model should provide a useful platform to analyze the effect of AML1/ETO on hematopoiesis and its potential cooperation with other mutations in the pathogenesis of leukemia.